Juvenile Xanthogranuloma: A Comparative Immunohistochemical Study of Factor XIIIa, CD11c, and CD4. (22nd July 2022) - Salari, Behzad; Dehner, Louis P.
Abstract: Juvenile xanthogranuloma is a group C and L non-Langerhans cell histiocytosis, and its cell of origin is still debatable. The expression of CD11c, a more recently described macrophage marker, and CD4 have not been studied comprehensively. This study aimed to expand immunophenotypic profile and hence our understanding of the origin of these lesions. The surgical pathology archive was searched for the cases with the pathologic diagnosis of "xanthogranuloma" from 1995 to 2019. Immunohistochemical (IHC) stains were performed for factor XIIIa, CD11c, and CD4. Morphologically, each lesion was classified into early classic, classic, or transitional subtypes. Seventy-seven cases were included with the median age of 7.8 years (male:female 1.3:1). Uniform positivity was noticed for CD4 (n = 77), CD68 (n = 37), CD163 (n = 5), and vimentin (n = 4) stains. Other stains included CD11c 75/77 (97.4%), factor XIIIa 71/76 (93.4%), S-100 protein 4/23 (17.4%), and CD1a 0/18 (0%). Despite insignificant association between morphologic subtype and main studied IHC stains, factor XIIIa reactivity was highest in transitional lesions and CD11c showed higher reactivity in early classic lesions. CD11c and CD4 are sensitive markers and showed promising results in the diagnosis of juvenile xanthogranuloma compared with factor XIIIa. Despite different reactivity of factor XIIIa and CD11c in various morphologic subtypes, such association was statistically insignificant.